A Nonfullerene Acceptor with Alkylthio‐ and Dimethoxy‐Thiophene‐Groups Yielding High‐Performance Ternary Organic Solar Cells. Issue 1 (3rd October 2019) - Zeng, Anping; Pan, Mingao; Lin, Baojun; Lau, Tsz-Ki; Qin, Minchao; Li, Kun; Ma, Wei; Lu, Xinhui; Zhan, Chuanlang; Yan, He
Abstract : Herein, an A–D–A‐type nonfullerene acceptor (named IDTS‐4F) with an alkyl thiophenyl side chain and dimethoxy thiophene bridging unit is reported. The use of an alkyl thiophenyl group is important, as the insertion of sulfur atoms can slightly downshift the highest occupied molecular orbital (HOMO) level of the molecule and allows IDTS‐4F to match with state‐of‐the‐art donor polymer PM6 (or PM7). Compared with conventional nonfullerene acceptors, IT‐4F, the IDTS‐4F molecule, has a smaller optical bandgap and higher lowest unoccupied molecular orbital (LUMO) level, which are beneficial to increase the V oc and J sc of the devices. Nonfullerene organic solar cell devices are fabricated using IDTS‐4F. Although the binary device based on IDTS‐4F exhibits a lower fill factor (FF, 70%), the ternary device by incorporating 0.2 of IDTS‐4F and 0.8 of IT‐4F (with PM6 as the donor polymer) can simultaneously achieve a higher V oc and J sc, while maintaining the high FF (77%) of IT‐4F based system. Morphology characterizations indicate the formation of homogeneous film morphology, the large increase in phase purity and crystallinity, and the reduction in domain size upon addition of crystalline IDTS‐4F, while the electron/hole mobilities and recombination losses of the IT‐4F system are both maintained. Abstract : A small‐molecule acceptor (IDTS‐4F) is designed for a ternary approach, which enables the simultaneous increase in open‐circuit voltage and short‐circuit current density without sacrificing fill factor. The two acceptors form homogeneous acceptor phases, which synergize them with the increase in phase purity and crystallinity and the reduction in domain size, whereas the charge mobilities and recombinations are maintained.